Un’Isola dal fragile equilibrio: Lampedusa fra l’impatto dei flussi di popolazioni e l’accoglienza sostenibile - Cancellieri, Adriano; Colloca, Carlo; Lipari, Licia; Lombardo, Elisa; Mazzette, Antonietta; Mugnano, Silvia; Spanu, Sara; Zizzari, Sara (SocietàMutamentoPolitica, 2020)
The paper presents the work done during the two editions of the Summer School that took place in Lampedusa in 2017 and 2018, organized by the Italian Association of Sociology – Environment and Territory Section. The aim of the paper is twofold. Firstly, it aims to illustrate the results of the data analysis and field observation carried out by the participants of the School. They consist of a multi-faceted description of the Island, with special attention to its different populations (residents, city users and especially migrants), and of some resulting project proposals. Secondly, the essay aims to promote a practice based on study and training, which is typical of the sociological analysis of territory, and that can provide useful insight on the studied places and to the people of Lampedusa, within a broader vision of justice and social sustainability.